2018
DOI: 10.15562/jdmfs.v3i2.625
|View full text |Cite
|
Sign up to set email alerts
|

Physical characteristics test (water content and viscosity) of extraction sodium alginate brown algae (phaeophyta) species padina sp. as basic material for production dental impression material

Abstract: Objective: This research aims to explore the potential of brown algae species padina sp. as a dental impression material by examining the physical characteristics of the sodium alginate extraction of brown algae species padina sp. Material and Methods:This research is a quasi-experimental with one-shot case study design. Samples are brown algae species padina sp. from Punaga and Puntondo beach in South Sulawesi. Brown algae species padina sp. is extracted to obtain sodium alginate and further tested for physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
(1 reference statement)
0
9
0
Order By: Relevance
“…Seaweed with a long thallus length will produce Na alginate with low viscosity, whereas if used with seaweed with a short thallus (20-40) cm it will produce high viscosity. Possible differences in the location where it grows is one of the causes of the difference in the value of the resulting viscosity (Hamrun 2018). The results of the alginate viscosity extracted from Sargassum polycystum are presented in Figure 9.…”
Section: Viscositymentioning
confidence: 99%
“…Seaweed with a long thallus length will produce Na alginate with low viscosity, whereas if used with seaweed with a short thallus (20-40) cm it will produce high viscosity. Possible differences in the location where it grows is one of the causes of the difference in the value of the resulting viscosity (Hamrun 2018). The results of the alginate viscosity extracted from Sargassum polycystum are presented in Figure 9.…”
Section: Viscositymentioning
confidence: 99%
“…The water content of the alginate produced from the research of Viswanathan and Nallamuthu [43] does not meet the quality standard of alginate quality which refers to the Food Chemical Codex (FCC) which is <15%. In the research of Hamrun and Rachman [39]; Herlina et al, [42]; Hamrun et al, [5,6]; and Kautsari and Ahdiansyah (2018) the percentage of water content is not reported. The high and low water content is influenced by the process of soaking the alginate with a solution during the extraction process.…”
Section: Water Contentmentioning
confidence: 95%
“…In the ash content parameter, the results ranged from 17.34%-31.24%. In the research of Hamrun and Rachman [39]; Herlina et al, (2016); Hamrun et al, [5,6]; and Kautsari and Ahdiansyah [47] the resulting ash content is not reported. The value of ash content is influenced by the washing process after the alginic acid formation process until the pH is close to a neutral number.…”
Section: Ash Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Indonesia is one of the countries with the longest and widest coastal area in the world and a country with abundant natural resources. One of Indonesia's leading commodities is seaweed [1]. The wealth of seaweed in Indonesia is about 769,452 ha.…”
Section: Introductionmentioning
confidence: 99%